MANNHEIM CURVES INn-DIMENSIONAL EUCLIDEAN SPACE - Öztekin, Handan; Metin, Esra (My University, 2017)
In this study, we de...ne the generalized Mannheim Curves in ndimensional Euclidean Space and obtain the caracterizations of the generalizedMannheim curves.
Keywords: Matematik